Nucleic acid synthesis in microsporocytes of Lilium cv. cinnabar: events in the nucleus. - Porter, E; Bird, J; Dickinson, H (1982)
In an electron microscopic autoradiographic study of DNA and RNA synthesis during meiosis isolated Lilium microsporocytes were supplied with [3H]thymidine and [3H]uridine. DNA synthesis occurred in the nucleus during the zygotene and pachytene intervals of meiotic prophase. Most of the activity was associated with the chromatin, but some synthesis early in zygotene was located at the nucleolus. RNA synthesis occurred throughout prophase until diplotene, when all activity ceased until after division. The newly synthesized RNA was found mostly in association with the chromosomal peripheries or in the space between chromosomes. There was also a peak of [3H]uridine incorporation at the nucleolus, which followed shortly after the synthesis of DNA at that site. The localization of DNA and RNA synthesis at the various stages of meiosis is discussed in relation to current concepts of chromosome pairing, crossing-over, ribosomal DNA amplification and cycles of RNA metabolism.